2007
DOI: 10.1245/s10434-007-9509-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Radioimmunotherapy and Hyperthermic Intraperitoneal Chemotherapy for the Treatment of Peritoneal Carcinomatosis of Colonic Origin in Rats

Abstract: Background: Cytoreductive surgery (CS) followed by heated intraperitoneal chemotherapy (HIPEC) is considered the standard of care for the treatment of patients with peritoneal carcinomatosis (PC) of colorectal cancer (CRC). These surgical procedures result in a median survival of 2 years at the cost of considerable morbidity and mortality. In preclinical studies, radioimmunotherapy (RIT) improved survival after CS in a model of induced PC of colonic origin.In the present studies we aimed to compare the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…Several studies on rodents have shown that radioimmunotherapy (RIT) is an efficient adjuvant after cytoreductive surgery for peritoneal carcinomatosis (7)(8)(9). Several IP RIT studies using strong b-or a-emitters are ongoing in animals (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Several studies on rodents have shown that radioimmunotherapy (RIT) is an efficient adjuvant after cytoreductive surgery for peritoneal carcinomatosis (7)(8)(9). Several IP RIT studies using strong b-or a-emitters are ongoing in animals (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…In a model with resected peritoneal carcinomatosis, the 177 Lu-MG1 antibody improved survival after cytoreductive surgery as compared to chemotherapy. 44, 45 Koppe et al also demonstrated the efficacy of RIT in peritoneal carcinomatosis after cytoreductive surgery. 49 In these studies, rats were first injected intraperitoneally with 2 · 10 6 CC-531 cells and tumors were allowed to grow for 14 days.…”
Section: Impact Of A-particles On the Peritoneummentioning
confidence: 98%
“…However, several recent studies have modeled minimal residual and metastatic disease in rat and mouse models and evaluated the efficacy of RIT. [38][39][40][41][42][43][44][45] Some of the models of minimal disease and the RIT strategies employed in these studies are schematically described in Figure 1.…”
Section: Impact Of A-particles On the Peritoneummentioning
confidence: 99%
“…6,9 The peritoneal perfusate consisting of 250 mL NaCl (0.9%) was warmed to 41.5°C and infused into the abdomen at 10 mL/min during 90 min. Mitomycin-C (Nycomed Christiaens BV, Breda, The Netherlands) was dissolved in saline and added to the perfusate in three separate gifts at 30 min intervals, each containing 50%, 25%, and 25% of the total dose of 35 mg/m peritoneal cavity.…”
Section: Hipecmentioning
confidence: 99%